Work process-related lead userness as an antecedent of innovative behavior and user innovation in organizations - Chia-huei Wu; Jeroen P.J. de Jong; Christina Raasch; Sabrine Poldervaart (Research Policy, 2020)
Recent studies have identified that employees can be lead users of their employing firm's products, and valuable sources of product innovation, residing within organizational boundaries. We extend this line of thought by recognizing that employees can be lead users with regard to internal work processes. We define work process-related lead userness (WPLU) as the extent to which employees experience unsatisfied process-related needs ahead of others, and expect high benefits from solutions to these needs. We hypothesize a positive association with user innovation in the workplace, evidenced by the development of tools, equipment, materials and methods. We test a moderated mediation model delineating how and when WPLU is related to user innovation within organizational boundaries. Drawing on survey data from 104 employees and 13 supervisors in a forensic services organization, we find that WPLU contributes to user innovation via engagement in innovative work behavior, especially when employees have higher self-efficacy (perceived capability to overcome obstacles) and lower job autonomy (situational constraints on the job).
Keywords: 330; Work process-related lead userness; Self-efficacy; Job autonomy; Innovative work behavior; User innovation